Legal advice on the Chinese compensatory fund system for oil pollution damage caused by ships from the perspective of marine environmental governance - Fu, Ben-Chao; Li, He-Ran (Frontiers in Marine Science, 2023)
As one of the primary obstructive factors for marine environmental governance, the frequent occurrence of oil pollution damage caused by ships has resulted in the establishment of compensation funds, such as the Oil Spill Liability Trust Fund of the United States, Ship Oil Pollution Fund of Canada and International Oil Pollution Compensation Fund (IOPC). Frequently suffering from marine oil pollution, China has extended considerable effort in marine environmental governance. Following the introduction of the ‘green principle’ into the Civil Code, China attached increasing significance to the legislation including compensation for oil pollution damage caused by ships. China formally established a compensation fund in 2012, and the past decade has witnessed the burgeoning development of the Chinese Ship-source Oil Pollution Compensation Fund (CSOPC), in addition to several defects which impede the fund from achieving the goal of marine environmental governance. As a national fund that is independent of the IOPC, the CSOPC adopts several regulations that are distinctive from internationally recognized practice; for instance, not recognizing pure economic loss within the scope of compensation. Such unique parameters, though partially originating from the national conditions in China, have resulted in glaring defects, including incomplete compensation scope and inappropriate compensation measures. Given the above problems, this study endeavours to provide several legal recommendations from the perspective of macro policies for improving the top-level design of the system, enhancing oil pollution compensation capabilities, and promoting the internationalization process. The study proposes two potential regulatory paths for innovation; namely, enlarging the range of compensation and establishing an essential emergency fund. From the perspective of protecting the rights of the victims of oil pollution damage and safeguarding the public interests of the ocean, this study puts forward relevant legal suggestions, which are expected to make valuable contributions to improving the compensation system for oil pollution damage caused by ships in China and promoting the governance of the marine environment.